Voluntary-Based Sociopreneurship Business Model in the GNJ Foundation (Gerakan of Nasi Jum'at): A Transformation - Triana Septiani; Dwi Prasetyani; Yuaninda Ajeng Prawesti; Tri Putri Kurniawati (International Journal of Science and Society, 2023)
Sociopreneursip (Social Entrepreneurship) plays an essential role in improving the community's economy. Sociopreneurship has several forms of business models, including a voluntary-based business model. Voluntary-based business models are usually applied to non-profit organizations such as foundations and NGOs (Non-Government Organizations). Sociopreneurship encourages economic development through community empowerment. This study looks at changes or transformations in the voluntary-based sociopreneurship business model and the implementation of sociopreneurship at the GNJ Foundation (Gerakan Nasi Jumat). The method used is qualitative with a case study approach. Data collection techniques through in-depth interviews, literature studies, and observation. This study explains that when GNJ entered its 3rd year, the sociopreneurship business model was transformed by mobilizing resources to develop an economic model and transforming the meaning of success for the founder. GNJ is classified as a voluntary-based sociopreneurship business model because GNJ provides social services voluntarily by carrying out main activities in the form of sharing appropriate food needs with marginal communities by paying attention to nutritional value and packaging that is not harmful. The GNJ Foundation applies the sociopreneurship concept identified in 4 elements. The first is that empowered entrepreneurs at GNJ can provide an economic turnaround for members in need and people experiencing poverty who are generally single-parent. The second is the idea/idea by making members and people experiencing poverty as food suppliers/suppliers in every GNJ activity, the third is the opportunity to create the GNJ Olshop WhatsApp group as a medium for business promotion and GNJ activities as a business target market, and fourth is the organization in which GNJ is a foundation that has a vision and mission and members. The sociopreneurship concept succeeded in creating sustainability at the GNJ foundation by empowering to increase economic income for members in need and people experiencing poverty who generally have single-parent status so that economic status improves and an attitude of mutual love is created without neglecting the primary purpose of this organization to share.